The role of team sports in fostering inclusivity and empathy among diverse student groups - Nof Yoffi AMIEL (Cross-Cultural Management Journal, 2023)

(untitled)
This article explores the role of team sports in fostering inclusivity and empathy among diverse student groups in the school sport context. While previous research has highlighted the potential of social education in physical education, this study focuses on the specific impact of team sports on social development. Drawing from relevant literature and empirical studies, we investigate how team sports provide a unique platform for students from different backgrounds to collaborate and learn together. The article delves into the effectiveness of cooperative teaching methods and their influence on promoting social assistance behavior and cooperation. Furthermore, we explore the concept of role theory and its relevance in enhancing social competence and conflict resolution skills in school sports. The significance of reflective teaching as a tool for encouraging positive social behaviors is also discussed. By emphasizing the importance of diversity, cooperation, and reflective practices, this article highlights the potential of team sports as a means to nurture well-rounded individuals who excel in sportsmanship and empathy.